2017
DOI: 10.1111/pce.12866
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic variation among six Arabidopsis thaliana accessions identified several novel genes controlling aluminium tolerance

Abstract: Differences in the expression levels of aluminium (Al) tolerance genes are a known determinant of Al tolerance among plant varieties. We combined transcriptomic analysis of six Arabidopsis thaliana accessions with contrasting Al tolerance and a reverse genetic approach to identify Al-tolerance genes responsible for differences in Al tolerance between accession groups. Gene expression variation increased in the signal transduction process under Al stress and in growth-related processes in the absence of stress.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…This suggests that protein processing in the ER is involved in Arabidopsis Al tolerance mechanisms. In fact, a gene encoding the ER-localized protein chaperon (BINDING PROTEIN3) was previously identified as one of the Al tolerant genes in Arabidopsis (Kusunoki et al, 2017). Expression level polymorphism of AtALMT1 and AtTRX1 due to cis-regulatory allelic variation was identified as one of the causes of Al tolerance variation detected by GWA mapping.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that protein processing in the ER is involved in Arabidopsis Al tolerance mechanisms. In fact, a gene encoding the ER-localized protein chaperon (BINDING PROTEIN3) was previously identified as one of the Al tolerant genes in Arabidopsis (Kusunoki et al, 2017). Expression level polymorphism of AtALMT1 and AtTRX1 due to cis-regulatory allelic variation was identified as one of the causes of Al tolerance variation detected by GWA mapping.…”
Section: Discussionmentioning
confidence: 99%
“…Expression level polymorphism is one of the mechanisms which causes phenotypic variation of Al tolerance among Arabidopsis accessions (Kusunoki et al, 2017). Using randomly chosen 25 accessions, we measured the expression level of four GWASdetected Al tolerance genes, AtALMT1, AtTRM28, AtTRX1, and AtSFR6, that showed more than 30% decrease of Al tolerance in the mutant compared to WT as shown in Figure 5, and analyzed the correlation between the ELP of tolerance genes and RRL Alassociated SNP (Figure 7).…”
Section: Expression Level Polymorphism Of Atalmt1 and Attrx1mentioning
confidence: 99%
See 1 more Smart Citation
“…The nutrient solution was renewed every 2 days. Subsequently, the seedlings were transferred to the Al stress solution (modified 2% MGRL without Pi, 10 μM AlCl 3 , pH 5.0) according to a previously described method (Kusunoki et al, 2017). After incubation for 9 hr under Al stress conditions, the roots of the seedlings were harvested and immediately frozen in liquid nitrogen.…”
Section: Rna Extraction and Measuring Gene Expression Levelmentioning
confidence: 99%
“…Differences in the expression levels of Al-tolerance genes influence the extent of Al tolerance in several important crops such as wheat ( Sasaki et al, 2004 ), rice ( Yamaji et al, 2009 ), and sorghum ( Magalhaes et al, 2007 ). Additionally, an analysis of expression level polymorphisms among Arabidopsis thaliana accessions identified several novel genes that regulate Al tolerance ( Kusunoki et al, 2017 ). In contrast, the identification and characterization of transcription factors and regulatory proteins (e.g., protein kinases) revealed that the transcription of Al-tolerance genes is likely regulated by a very complex mechanism.…”
Section: Introductionmentioning
confidence: 99%